Sturearkivets väg till Danmark - Retsö, Dag (Historisk Tidsskrift, 2019)
When, how and why was the Sture archive brought to Denmark? This article explores the issue of when, how and why the Sture archive, the single largest Swedish letter collection from the Middle Ages, disappeared from Sweden and ended up in Denmark, where it was preserved until 1929. Hitherto, it has been believed that the archive was carried by Swedish archbishop Gustav Trolle and Danish bishop Jens Andersen (Beldenak) in September 1521, as they fled from the approaching rebel forces of Gustav Eriksson (Vasa). However, this view is based on the dubious assumptions that the modern archive constitutes one organic archive entity and that it was under the custody of the chancellor of the Swedish realm, a function held by Jens Andersen at the time. It is shown that the Sture archive, as it is found in the Swedish National Archives today, is comprised of several parts that were brought to Denmark in different ways and at different times, beginning in 1508 and possibly continuing until1523. The core of the letter collection, i. e., the archives of the national regents Svante Nilsson (1504–1512) and Sten Sture the younger (1512–1520), was probably taken out of Sweden on two different occasions. One group of letters from Sten Sture’s archive, predominantly documents concerning the accolade of Kristian II as the king of Sweden and Sweden’s relations to towns of the Hanseatic League, was separated from the rest of the collection in the autumn of 1520 and taken to Denmark a year later on direct order from the king by his trustee Didrik Slagheck, and subsequently disappeared. The remainder, the larger part of the regents’ archives, followed the same way on a later occasion, most probably not on the king’s order or even with his knowledge, but through the private initiative of an unknown person shortly before the accession of Gustav Vasa as the king of Sweden. Gustav Trolle and Jens Andersen had probably nothing to do with it. The fact that nothing at all is known about the archive in Denmark during the first centuries after the 1520s indicates that it has not been in possession of the keepers of the royal archives there. Instead, it is more likely that it had been kept by a private person until sometime before the 1750s, which probably explains why it still exists today.